NON-GENETIC FACTORS AFFECTING THE MORTALITY IN KURDI LAMBS - O. Raoof, S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was carried out using 94 ewes at Erbil plain - Kurdistan region-Iraq, during the period from May 2016 to April 2017. The overall mean mortality rates from birth to 7 days and from 8 days to weaning age were 8.6 and 6.6%, respectively. Age of dam, type of birth, weight of the dam at matting, Body Condition Score (BCS) and birth weight had an important significant (P<0.05) impact on lamb mortality from birth to 7 days and from 8 days to weaning age. This research revealed that a higher lamb mortality (4.2%) was registered for dams aged 2 years, while a lower mortality(6.6%) was found in dams aged 5-6 years, no significant differences in mortality among males and females were appeared, male lambs showed a higher mortality than females, type of birth showed an important impact (P<0.05) on lamb mortality. Single born lamb mortality was 5.5%, whereas that of the twin born lamb was significant (13.6%). Ewes with the (BCS) of 2-3 showed a higher mortality (14.2%), while those ewes with (BCS) more than 3 recorded the lowest lamb mortality (5.4%). Lambs weighting less than 3 kg at birth registered a higher mortality compared with lambs weighing 3 kg, or more which showed the lowest mortality. It has appeared from the results of this study that most of the non-genetic factors studied involve: Age of dam, type of birth, birth weight, and weight of the dam, and body condition score showed a substantial significant influence on lamb mortality between birth and weaning of Kurdi sheep.